"WE EVEN FORGET THAT WE'RE NURSES": IDENTITY PERSPECTIVES OF NURSES IN PSYCHOSOCIAL CARE CENTERS - Tâmara da Cruz Piedade Oliveira; Deybson Borba de Almeida; Gilberto Tadeu Reis da Silva; Denise Lima da Silva Brasileiro (Universidade Federal do Paraná, 2023)
Objective: To analyze the interface between the nurse's professional identity and her work process in mental health. Method: An exploratory, qualitative study was conducted in six Psychosocial Care Centers in Salvador - Brazil. The data was collected between June and August 2022 through interviews with ten nurses and was subjected to thematic analysis. Results: the thematic analysis resulted in one category: Identity conflicts and ambiguities, with the themes "Core know-how and the identity of the 'traditional nurse'" and "Field know-how and the vagueness of identity contours". Conclusion: The results point to the need for more in-depth research into the nurse's know-how, which includes the fulfillment of her private activities that are congruent with the production of care in the field of psychosocial care.